The integration of two generations in a vietnamese family living in the czech republic = Sự hòa nhập của hai thế thệ trong một gia đình người việt đang sinh sống tại Tiệp Khắc - Phạm, Thị Phương Anh (ĐHQGHN - Trường Đại học Ngoại Ngữ, 2021)
This study was set out to examine the adaptation strategies of two different generations in a Vietnamese family living in the Czech Republic. In order to comply with the objective, a theoretical framework was adopted to measure four types of adaptation process. To be more specific, in order to gather necessary data for the research, different documents about adaptation process were collected for observation, and four semi- structured interviews were hold to collect the audience’s data. The results from analysis revealed that ‘integration’ was the strategy chosen by both two generations in the Vietnamese family. There are many factors including individual influences and contextual influences which may affect the adaptation process and the selection of adaptation strategies of immigrants. Moreover, the successful adaptation of the first generation can also lead to the success of the second generation. This paper can be improved by inviting more participants to the research. The more audiences participate in the survey, the more various the collected data gets. Then, there might appear changes in the selection of the host society.